Glucocorticoid trajectories over 2 years in patients with rheumatoid arthritis in a real-life setting - Martin Soubrier; Bruno Pereira; Sylvain Mathieu; Marion Couderc; Anne Tournadre; Sandrine Malochet-Guinamand; Céline Lambert; Alycia Delteil; Marie Eva Pickering; Marc Villedon (RMD Open, 2023)
Objectives To analyse glucocorticoid (GC) use and trajectories in a real-life cohort of rheumatoid arthritis (RA).Methods Patients with RA included in the longitudinal RCVRIC cohort for initiating or changing biological disease-modifying antirheumatic drugs, were compared for the use of GCs at baseline. Among the GC users, the GC dose was analysed over 2 years of follow-up by group-based trajectory models. Characteristics and outcomes were compared between the trajectories.Results Among the 184 patients (RA duration 4.2 years (1.3; 12.6), Disease Activity Scores (DAS)28-C reactive protein (CRP) 4.24±2.14), 81 (44%) were on GCs. The GC users were significantly older, had higher CRP and Health Assessment Questionnaire (HAQ), more hypertension and lower lumbar T-score, but similar activity and erosive scores. Among the GC users, two trajectories were identified: trajectory 1 (n=20, 25%) with GC discontinuation in the first year and trajectory 2 (n=61, 75%) with maintenance of low-dose GCs at 2 years. Trajectory 2 was significantly associated with higher HAQ, a longer GC duration and a less frequent methotrexate association. After adjustment for HAQ, GC duration and MTX use, good EULAR responses were less frequent at 6 months and 1 year in the GC maintenance trajectory (38.3% vs 81.3%, p=0.03; 42.0% vs 82.4%, p=0.02). Diabetes, fractures and increased body mass index were noted in trajectory 2.Conclusion GCs were used in almost half of patients with established RA in real-world practice. For the majority of GC users, a long-term low dose of GCs is maintained over 2 years. These results highlight the difficulties with stopping GCs, the lack of consensus for the efficacy–safety balance of GCs, and the need to individualise the best GC tapering.